Seventeenth-century Gdansk instrumental music sources - Szlagowska, Danuta (Interdisciplinary Studies in Musicology, 2018)
This article represents an attempt to provide a synthetic presentation of seventeenth-century Gdańsk instrumental music sources, comprising three groups: 1 - manuscripts and old prints, currently found in Gdańsk or elsewhere, that include works by musicians who were active in Gdańsk; 2 - manuscripts from Gdańsk libraries that include works by composers not active in Gdańsk; 3 - manuscripts of Gdańsk provenance, now held in libraries outside Gdańsk, that include works by composers not active in Gdańsk. Several types of sources have survived that are characteristic of the age in which they were created. These include lute tablatures, keyboard tablatures and manuscripts and old prints with compositions for various forces, including keyboard instruments, solo instruments (violin, cornet) with b.c., a 2 and a 3 type compositions for violin (in one case for cornet and bassoon with b.c.) and also larger ensembles, chiefly strings with b.c. The repertoire of the Gdańsk sources is similar to that of other seventeenthcentury European sources. It includes dances, canzonas, fantasias, preambles, sonatas, suites and, in the earliest manuscripts, intabulations of both religious and secular songs. In total, there are some 800 extant compositions, of which the vast majority (around 700) are found in lute and keyboard tablatures. Some compositions may be considered unique in Old Polish instrumental music. They are works by the composers Marcin Gremboszewski and Heinrich Dóbel, who were active in Gdańsk, representing early examples of solo compositions for cornet and violin with b.c., as well as a chamber piece for cornet and bassoon with b.c. Bearing in mind that the number of extant Old Polish instrumental music sources is relatively modest, these Gdańsk sources should be considered a highly valuable supplement.